Analisa Pengaruh Idiosinkratik Islam Karimov Terhadap Sistem Kerja Paksa Sektor Industri Kapas di Uzbekistan - Chintya Kusumawardany; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2022)
This research was made to discuss the problem of forced labor in Uzbekistan which is forced labor systemized by the state. The purpose of this study was to find out how Islam Karimov's leadership style and its influence on forced labor policies that occurred in the Uzbekistan cotton industry sector through the formalistic leadership style and aggressive personality typology according to Margaret Hermann. This study discusses how in determining a policy, the factors that are within Islam Karimov and the environment in which he lives and Islam Karimov's politics have an influence which is analyzed using idiosyncratic theory. The author uses qualitative research methods with qualitative descriptive research. The results of the author's research conclude that Islam Karimov uses forced labor in Uzbekistan as an effort to stabilize the Uzbekistan economy and make Uzbekistan an independent country after separating from the Soviet Union.